Avaliação dos minérios itabiritos compactos e semi-compactos em um circuito de britagem da Samarco Mineração S/A - Lamartine da Silva Freitas (2014)
At Samarco Mineração S.A. the present reserves of Alegria mines consist of four types of itabirite: friable, compact specularitic, semi compact specularitic, and semi compact non specularitic. The semi compact specularitic and non specularitic itabirites and the compact specularitic itabirite represent 37% of the reserves totalizing 1.04 billion tonnes. The first target of this study was the determination of chemical characteristics, size distribution, and liberation degree of the samples. The next step was the evaluation, from crushability and screening tests, of simulations of crushing circuits. The present work also addresses the compact non specularitic itabirites that were considered waste since 2013. The proposed circuit for the tests was based on the conventional crushing circuit at concentrador I. Five samples were prepared, classified as compact specularitic itabirite (+ 9,5mm > 80%), compact non specularitic itabirite (+9,5mm > 80%) semi compact specularitic itabirite (+9,5mm > 60% to 80%), and a friable itabirite sample called standard or reference sample (+9,5mm <40%). The results indicated that the iron content and the liberation degree of the problem samples are lower than the figures for the reference sample. The semi compact and compact specularitic itabirites and the non specularitic itabirites present a much coarser size distribution in comparison with the reference sample. Regarding the crushability and screening tests, the results indicated that it is almost impossible to process semi compact specularitic or non specularitic itabirites and compact specularitic itabirites individually in the crushing plant of concentrator 1.